Induction of Endogenous Virus and of Thymidine Kinase by Bromodeoxyuridine in Cell Cultures Transformed by Friend Virus - Ostertag, W. (1974)
Thymidine kinase positive (TK(+)) N type cell lines that had been transformed by spleen focus-forming virus were established by transformation with NB tropic Friend virus complex. Thymidine kinase deficient (TK(-)) cell clones were isolated. Some of these cell clones release 1000- to 100,000-fold reduced amounts of Friend virus complex as compared to the TK(+) parental cell clone. TK(-) clones were grown in medium without BrdUrd. Some of these TK(-) clones can be induced to release endogenous helper virus and transforming spleen focus-forming virus on reexposure to 10(-6)-10(-4) M BrdUrd. The induced Friend virus complex is of N host range as expected with induced endogenous virus in N-type cells. Before the induction of the endogenous virus spleen focus-forming virus complex, an induction of thymidine kinase (ATP:thymidine 5′-phosphotransferase, EC 2.7.1.75) activity is observed. The latter is possibly a prerequisite for the induction of endogenous virus in TK(-) cells. Induction of thymidine kinase activity and of endogenous virus is transient and always correlated. The role of BrdUrd and another thymidine analogue, azidothymidine, in interfering with C-type virus release in virus positive cells is discussed. Azidothymidine is unable to induce endogenous virus. Induction of endogenous virus by BrdUrd and inhibition of virus release in virus positive cells is apparently not caused by the same mechanism.